Development of an indirect ELISA for the identification of African swine fever virus wild-type strains and CD2v-deleted strains - Jiang, Wenting; Jiang, Dawei; Li, Lu; Wan, Bo; Wang, Jiabin; Wang, Panpan; Shi, Xuejian; Zhao, Qi; Song, Jinxing; Zhu, Zixiang; Ji, Pengchao; Zhang, Gaiping (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a potent infectious disease with detrimental effects on the global swine industry and no currently vaccine available. The emergence of low-intensity CD2v deletion mutants manifested as non-hemadsorption (non-HAD) strains represents a significant challenge to the prevention and control of ASF. In this study, we aimed to establish an indirect ELISA (iELISA) method for the identification of ASFV wild-type and CD2v deletion strains. We integrated the CD2v protein extracellular domain sequence (CD2v-ex, 1–588 bp) of the highly pathogenic strain China/2018/AnhuiXCGQ into the genome of suspension culture-adapted Chinese hamster ovary (CHO)-S cells using lentivirus vectors (LVs). By screening, we identified a monoclonal CHO-S cell line that stably expressed secretory CD2v-ex protein. We then used the purified CD2v-ex protein as the detection antigen to establish an indirect ELISA method (CD2v-iELISA) for identification of the ASFV wild-type and CD2v deletion (CD2v-) strains. The CD2v-iELISA method showed excellent specificity with no cross-reaction with serum samples infected with ASFV (CD2v-), porcine reproductive and respiratory syndrome virus (PRRSV), classical swine fever virus (CSFV), porcine circovirus (PCV), porcine pseudorabies virus (PRV), swine foot and mouth disease virus (FMDV) and porcine epidemic diarrhea virus (PEDV). Furthermore, this method showed high sensitivity, allowing identification of ASFV-infected clinal serum samples up to a dilution of 1:2,560. The coefficient of variation both in and between batches was <10% with good reproducibility and a high compliance rate of 99.4%. This CD2v-iELISA method developed here is of great significance for the prevention, control and purification of ASFV.